A COMPOSITE AND A METHOD OF PREPARING THE SAME - ZHANG, Yugen; WANG, Jinquan (2021)
There is provided a composite comprising an inorganic metal or alloy core at least partially covered by a protection layer comprising a carboxylate salt, a metal oxide, a metal oxide salt or a metal-amino acid complex. There is also provided a method of preparing the composite comprising an inorganic metal or alloy core at least partially covered by a protection layer comprising a carboxylate salt, a metal oxide, a metal oxide salt or a metal-amino acid complex, comprising the step of mixing a metal or alloy with an acid, at elevated temperature for a time duration, optionally in the presence of a solvent. There is also provided use of a composite as an antimicrobial agent, and uses of a composite in the treatment or prophylaxis of microbial infection. There is also provided a method of inhibiting microbial activity or treating a microbial infection or disease comprising administering an antimicrobial composition comprising said composite as disclosed herein to a subject or applying the antimicrobial composition on a surface.